2008
DOI: 10.1186/1475-2875-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for house-entry by malaria vectors in a rural town and satellite villages in The Gambia

Abstract: Background: In the pre-intervention year of a randomized controlled trial investigating the protective effects of house screening against malaria-transmitting vectors, a multi-factorial risk factor analysis study was used to identify factors that influence mosquito house entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 37 publications
11
147
0
Order By: Relevance
“…If CDC light traps are to be used as a replacement for indoor HLCs, it would be impractical and unethical in an area with high ITN use to replace all existing nets with untreated bed nets for monitoring purposes. Previous studies have shown a slight decrease in 8 or no effect on 28 the sampling efficiency of CDC traps in the presence of ITNs. However, although surrounding occupied beds were covered with ITNs, the CDC traps in both of these investigations were hung next to untreated bed nets.…”
Section: Discussionmentioning
confidence: 85%
“…If CDC light traps are to be used as a replacement for indoor HLCs, it would be impractical and unethical in an area with high ITN use to replace all existing nets with untreated bed nets for monitoring purposes. Previous studies have shown a slight decrease in 8 or no effect on 28 the sampling efficiency of CDC traps in the presence of ITNs. However, although surrounding occupied beds were covered with ITNs, the CDC traps in both of these investigations were hung next to untreated bed nets.…”
Section: Discussionmentioning
confidence: 85%
“…Six sentinel rooms in 32 clusters, where a consenting adult slept under a bednet, were sampled monthly in both transmission seasons. Potential risk factors known to affect mosquito densities in The Gambia 29 were recorded at each collection. Mosquitoes were killed by freezing before morphological identification by standard keys 30,31 and unfed and blood-fed mosquitoes were dissected to determine whether they were parous.…”
Section: Entomological Collectionsmentioning
confidence: 99%
“…Screening was highly effective in reducing overall indoor mosquito density by 40% in Ethiopia, [60] 59% in Gambia [61] and a reduction in incidence of malaria and prevalence of anaemia. [62] Fitting nets or metal mesh on windows and a secondary door (automatically controlled by an elastic band or iron spring), could reduce mosquitoes entering houses.…”
Section: Strategies To Address Community Educationmentioning
confidence: 99%
“…[64] It has dual benefits of preventing entry of mosquitoes and other potentially harmful organisms while at same time keeps houses airy (when eaves are closed with mesh), hence, highly acceptable. [61] Also, screening has no gender inequity concerns because protection does not target individuals. [65] The possibility of using expired ITNs [64] and locally affordable and accessible materials like mud, palms and sticks, [60,63] makes screening highly financially feasible and highly sustainable.…”
Section: Strategies To Address Community Educationmentioning
confidence: 99%